Evaluation of Nesting Care on the Stability of Physiological Parameters (Respiratory Rate, Oxygen Saturation, Heart Rate, And Body Temperature) in Low Birth Weight (LBW) Infants in The Perinatology Unit - Andini Eka Putri Zulkarnaen; Susiana Jansen (Jurnal Ilmiah Global Education, 2026)
This study aimed to evaluate the effectiveness of nesting care in stabilizing physiological parameters of low birth weight infants receiving treatment in a perinatology unit. A descriptive case study design was used to observe two premature infants who experienced respiratory instability, fluctuating body temperature, feeding intolerance, and a high risk of infection. Nesting care was applied continuously for three days by positioning the infants in a flexed posture resembling the intrauterine environment to improve comfort and reduce physiological stress. Physiological parameters, including heart rate, respiratory rate, oxygen saturation, and body temperature, were monitored before and after the intervention. The results showed consistent improvement in both infants, marked by decreased heart rate and respiratory rate, increased oxygen saturation reaching ninety nine percent, and stable body temperature within the normal range. These findings indicate that nesting care supports physiological stabilization and promotes energy conservation in infants with low birth weight. In conclusion, nesting care is a simple, affordable, evidence based intervention that enhances physiological stability and can be integrated into routine neonatal nursing practice.